RANCANGAN STRATEGI PENGEMBANGAN USAHA COFFEE SHOP MENGGUNAKAN METODE QUANTITATIVE STRATEGIC PLANNING MATRIX (QSPM) DAN BLUE OCEAN STRATEGY (BOS) DALAM UPAYA MEMPERTAHANKAN USAHA (STUDI KASUS: MEDIAN COFFEE AND EATERY) - Ibnu Arbie Natama Rambe; Muhammad Ihsan Hamdy; Ismu Kusumanto; Misra Hartati; Harpito Harpito (JURNAL PERANGKAT LUNAK, 2023)
The increasing number of coffee shops in Pekanbaru city significantly makes Median Coffee and Eatery required to remain competitive by determining the right planning / strategy. In the last few months Median Coffee and Eatery has experienced a very significant decline in profits. This study aims to design alternative strategies by providing new innovations in developing and maintaining businesses using the Quantitative Strategic Planning Matrix (QSPM) and Blue Ocean Strategy (BOS) methods. Based on the results of calculations using the QSPM method, 7 alternative strategies were obtained, there are 3 priority strategies that have the highest TAS value, namely providing an attractive outdoor area (TAS 7.647), expanding indoor and parking areas (TAS 7.643), and optimizing promotional activities (TAS 7.559). This research is expected to be an evaluation and consideration for business owners so that Median Coffee and Eatery can increase sales.